Property rights, institutional regime shifts and the provision of freshwater ecosystem services on the Pongola River floodplain, South Africa. Issue 1 (March 2017) - Nkhata, Bimo Abraham; Breen, Charles; Hay, Duncan; Wilkinson, Melanie
This paper proposes a property rights perspective to interpret institutional regime shifts in the provision of freshwater ecosystem services. Institutional regime shifts are conceived as persistent changes in the structure and function of a system. Property rights are viewed as an important component of institutional regimes. The paper draws on a case study of flow regulation on the Pongolo Floodplain in South Africa to illustrate the central role of property rights in mediating institutional regime shifts. The case study illustrates that there are many combinations of property rights that underpin institutional regime shifts in the provision of freshwater ecosystem services. It provides useful insights into the consequences of failing to recognize, establish and enforce bundles of rights. A major thrust of the case study is that the nature and context of property rights are important in determining the long-term provision of these services. By examining the configurations of property rights that have governed the Pongola River floodplain over the years, the paper demonstrates the importance of explicitly defining and categorizing the range of rights.